Associations between clusters of maternal or paternal characteristics and offspring adiposity in late adolescence - Marina Ybarra; Andraea Van Hulst; Tracie A. Barnett; Lynn Meng; Tasneen Zaihra; Marie-Eve Mathieu; Mélanie Henderson (BMC Pediatrics)
Abstract Background Several parental behaviors that contribute to social norms, such as physical activity, are linked to offspring obesity. No prospective study has examined the impact of combined behavior profiles on adiposity in offspring. We examined whether clusters of maternal or paternal social-behavioural factors are associated with subsequent adiposity in offspring in late adolescence. Methods Data were obtained from the QUALITY Cohort, a longitudinal study of children with at least one biological parent with obesity (n = 630). Maternal and paternal characteristics were collected at baseline when participants were 8–10 years old, and adiposity outcome measures (body mass index z-score (zBMI), android/gynoid fat ratio (A/G ratio), % body fat (%BF), fat mass index (FMI)) were obtained for the offspring at 15–17 years of age. Parental smoking, physical activity and education were self-reported. Both parental and child weight and height were measured by trained nurses, and BMI was calculated. Additional child adiposity measurements were obtained using dual energy X-ray absorptiometry. Analyses were performed for 209 families with complete data across both evaluation cycles. Cluster analysis was used to identify distinct maternal and paternal clusters based on BMI, PA, education and smoking habits at baseline. Multivariable regression models adjusted for offspring age, sex and Tanner stage were used to estimate associations between maternal and paternal clusters and offspring adiposity outcomes. Results Three distinct clusters were identified among mothers, and four were identified among fathers. Mothers in the first cluster (n = 18) had obesity and lower educational attainment, were smokers, and reported more physical activity; those in the second cluster (n = 109) had overweight, higher educational attainment and were nonsmokers; and those in the third cluster (n = 82) had overweight, lower educational attainment, were nonsmokers, and reported the least physical activity. The offspring of mothers in the first cluster had consistently higher adiposity across all outcome measures, including zBMI, FMI, %BF, and A/G ratio, than did those in the second cluster (e.g., for zBMI β [ 95%CI]= 0.94, [0.35,1.53], p-value = 0.01). Offspring adiposity levels were comparable across paternal clusters. Conclusions Children of mothers with a specific risk factor combination (obesity, lower educational attainment and smoking) had greater adiposity by adolescence.